2017
DOI: 10.1176/appi.ps.201600329
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of the Rochester Forensic Assertive Community Treatment Model

Abstract: The Rochester FACT model was associated with fewer convictions for new crimes, less time in jail and hospitals, and more time in outpatient treatment among justice-involved adults with psychotic disorders compared with treatment as usual.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(85 citation statements)
references
References 50 publications
2
82
0
1
Order By: Relevance
“…For example, Patel et al demonstrated the successful delivery of behavioral activation for depression by LHWs through relatively brief training to a population with significant barriers to healthcare access [ 91 •]. Some studies adapted evidence-based models (e.g., Forensic Assertive Community Treatment) to deliver treatments in non-traditional locations, such as jails, churches, and senior centers [ 77 ]. Many individual-level interventions also simultaneously acted at the organizational/institutional level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Patel et al demonstrated the successful delivery of behavioral activation for depression by LHWs through relatively brief training to a population with significant barriers to healthcare access [ 91 •]. Some studies adapted evidence-based models (e.g., Forensic Assertive Community Treatment) to deliver treatments in non-traditional locations, such as jails, churches, and senior centers [ 77 ]. Many individual-level interventions also simultaneously acted at the organizational/institutional level.…”
Section: Discussionmentioning
confidence: 99%
“…In Monroe County, New York, adults with psychotic disorders charged with misdemeanors were conditionally released and randomized to usual treatment ( n = 35) or Forensic Assertive Community Treatment (FACT) ( n = 35) [ 77 ]. FACT employed high-fidelity ACT services with the following adaptations: a 6-h training in criminal justice collaboration for clinicians, screening for criminogenic risk factors among enrollees, weekly court appearances, and meetings to discuss barriers to success with the supervising judge, public defender, and district attorney.…”
Section: Criminal Justicementioning
confidence: 99%
“…Such “step-down programs” also offer a gradual increase in behavioral interventions and incentives (such as out-of-cell time) to help inmates successfully prepare for general inmate population and release into community ( 81 ). Finally, upon release, intensive case-management of all releasees or forensic assertive community treatment for inmates with lasting mental illness could also reduce subsequent criminal justice involvement and hospitalizations in releasees ( 84 ).…”
Section: Discussionmentioning
confidence: 99%
“…ACT and its variants offer a related strategy to assist people at the margins of the criminal justice and mental health systems (Morrissey, Meyer, and Cuddeback 2007;Lamberti et al 2017;Calsyn et al 2005). This is a challenging assignment.…”
Section: Assertive Community Treatment (Act)mentioning
confidence: 99%